How the care workforce navigates the digital ‘skills gap’: problems and opportunities from policy to practice - Whitfield, Grace; Kispeter, Erika; Hamblin, Kate; Burns, Diane (Frontiers in Sociology, 2025)
IntroductionCare systems and services across the globe are under pressure, with challenges related to the recruitment and retention of the care workforce identified as a particular issue. In England, digital technologies are presented in policy discourse and strategy as a potential way to navigate these complexities by delivering faster, cheaper and better care. The workforce, meanwhile, tends to be defined as requiring better digital skills to enable the full potential of digital technologies to be realised.MethodsWe carried out qualitative case study research of seven social care provider organisations, involving interviews with a total of 62 people from a range of roles across the care workforce and observations of work-based practices. Drawing on this data, we explore in-depth the workforce’s experiences of and perspectives on using new technologies, and the requisite skills.ResultsThe results show how the issue of maximising the adoption of technologies is (1) affected less by a deficit in worker skills, and more by the type of digital technologies in use, the job role of the worker, and the type of care provider, (2) can be facilitated by a supportive learning environment, and (3) can be impeded by issues in the functionality of systems and devices.DiscussionWe show a disconnect between the assumptions made in policy discourse and the practicalities and variations in how workers adapt, apply, and develop skills. We also explore the importance of peer support, albeit hindered by time constraints and sometimes overly relying on individual workers. In addition, the paper highlights the importance of understanding how new technology adoption can be stymied by the design of the technology itself, rather than the result of the workforce’s lack of digital skills per se. An unintended consequence of defining the problem as a skills mismatch and the solution as skilling the workforce is that the abilities of the workforce to creatively and flexibly manage the short-comings of digital devices and systems are overlooked and under-utilised - reflecting a wider failure to acknowledge and compensate care workers’ skills.